Determinants of Current Account Deficits in Developing Countries - Calderon, Cesar; Chong, Alberto; Loayza, Norman (World Bank, Washington, DC, 2014)
The authors examine the empirical links between current account deficits and a broad set of economic variables proposed in the literature. To accomplish this, they complement and extend previous research by using a large, consistent set of macroeconomic data on public and private domestic savings, external savings, and national income variables; focusing on developing economies by drawing on a panel data set for 44 developing countries and annual information for the period 1966-95; adopting a reduced-form approach rather than holding to a particular structural model; distinguishing between within-country and cross-country effects; and employing a class of estimators that controls for the problems of simultaneity and reverse causation. Among their findings: Current account deficits in developing countries are moderately persistent. A rise in domestic output growth generates a larger current account deficit. Increases in savings rates have a positive effect on the current account. Shocks that increase the terms of trade or cause the real exchange rate to appreciate are linked with higher current account deficits. Either higher growth rates in industrial economies or higher international interest rates reduce the current account deficit in developing economies.